Saving and wealth inequality - Mariacristina De Nardi; Giulio Fella (Queen Mary University of London, School of Economics and Finance, 2017)
Why are some people wealth rich while others are poor? To what extent can governments affect inequality? Which instruments should they use? Answering these questions requires understanding why people save. Dynamic quantitative models of wealth inequality can help us to understand and quantify the determinants of the outcomes that we observe in the data and to evaluate the consequences of policy reform. This paper surveys the savings mechanisms generated by the transmission of bequests and human capital, by preference heterogeneity, by rate of return heterogeneity, by entrepreneurship, by richer earnings processes, and by medical expenses. It concludes that the transmission of bequests and human capital, entrepreneurship, and medical-expense risk are crucial determinants of savings and wealth inequality and that we need to look at more data to measure their relative importance.
Keywords: E21; D14; D3; 330; Human Capital; Bequests; Taxation; Entrepreneurship; Rates of Return; Earnings Shocks